Association between treatment with oral third‐generation cephalosporin antibiotics and mortality outcomes in Ebola virus disease: a multinational retrospective cohort study. Issue 4 (22nd January 2020) - Aluisio, Adam R.; Perera, Shiromi M.; Yam, Derrick; Garbern, Stephanie; Peters, Jillian L.; Abel, Logan; Cho, Daniel K.; Woldemichael, Dayan; Kennedy, Stephen B.; Massaquoi, Moses; Sahr, Foday; Liu, Tao; et al.
Abstract: Objective: To evaluate the association between oral third‐generation cephalosporin antibiotic treatment and mortality in Ebola virus disease (EVD). Methods: This retrospective cohort studied EVD‐infected patients admitted to five Ebola Treatment Units in Sierra Leone and Liberia during 2014–15. Empiric treatment with cefixime 400 mg once daily for five days was the clinical protocol; however, due to resource variability, only a subset of patients received treatment. Data on sociodemographics, clinical characteristics, malaria status and Ebola viral loads were collected. The primary outcome was mortality compared between cases treated with cefixime within 48 h of admission to those not treated within 48 h. Propensity scores were derived using clinical covariates. Mortality between treated and untreated cases was compared using propensity‐matched conditional logistic regression and bootstrapped log‐linear regression analyses to calculate an odds ratio (OR) and relative risk (RR), respectively, with associated 95% confidence intervals (CI). Results: Of 424 cases analysed, 360 (84.9%) met the cefixime treatment definition. The mean age was 30.5 years and 40.3% were male. Median cefixime treatment duration was 4 days (IQR: 3, 5). Among cefixime‐treated patients, mortality was 54.7% (95% CI: 49.6–59.8%) vs . 73.4% (95% CI: 61.5–82.7%) in untreated patients. In conditional logistic regression, mortality likelihood was significantly lower among cases receiving cefixime (OR = 0.48, 95% CI: 0.32–0.71; P  = 0.01). In the bootstrap analysis, a non‐significant risk reduction was found with cefixime treatment (RR = 0.82, 95% CI: 0.64–1.16, P  = 0.11). Conclusion: Early oral cefixime may be associated with reduced mortality in EVD and warrants further investigation. Abstract : Objectif: Evaluer l'association entre le traitement antibiotique oral avec des céphalosporine de troisième génération et la mortalité dans la maladie au virus Ebola (MVE). Méthodes: Cette étude de cohorte rétrospective a été menée chez des patients infectés par la maladie au virus Ebola admis dans cinq unités de traitement Ebola en Sierra Leone et au Libéria en 2014–2015. Le traitement empirique avec Cefixime 400 mg une fois par jour pendant cinq jours était le protocole clinique. Cependant, en raison de la variabilité des ressources, seul un sous‐ensemble de patients a reçu un traitement. Des données sur la sociodémographie, les caractéristiques cliniques, le statut du paludisme et les charges virales d'Ebola ont été collectées. Le critère principal était la mortalité comparée entre les cas traités au céfixime dans les 48 heures suivant l'admission et ceux non traités dans les 48 heures. Les scores de propension ont été dérivés à l'aide de covariables cliniques. La mortalité entre les cas traités et non traités a été comparée à l'aide d'analyses de régression logistique conditionnelle et de régression log‐linéaire bootstrapées pour calculer respectivement un rapport de cotes (OR) et un risque relatif (RR), avec des intervalles de confiance (IC) à 95% associés. Résultats: Sur 424 cas analysés, 360 (84, 9%) répondaient à la définition du traitement au céfixime. L'âge moyen était de 30, 5 ans et 40, 3% étaient des hommes. La durée médiane du traitement par le céfixime était de 4 jours (IQR: 3, 5). Parmi les patients traités au Cefixime, la mortalité était de 54, 7% (IC95%: 49, 6 à 59, 8%) vs 73, 4% (IC95%: 61, 5 à 82, 7%) chez les patients non traités. Dans la régression logistique conditionnelle, la probabilité de mortalité était significativement plus faible parmi les cas recevant du céfixime (OR = 0, 48 ; IC95%: 0, 32 à 0, 71; P = 0, 01). Dans l'analyse bootstrap, une réduction du risque non significative a été trouvée avec le traitement au céfixime (RR = 0, 82, IC95%: 0, 64 à 1, 16 ; P = 0, 11). Conclusion: Le céfixime par voie orale rapide peut être associé à une mortalité réduite dans la MVE et mérite une investigation plus approfondie.